The identity of Lotus antiochianus and taxonomic limits of Lotus and Hammatolobium (Leguminosae: Loteae) - Sokoloff, Dmitry; Kramina, Tatiana (Phytotaxa, 2016)
The recently described species Lotus antiochianus İlçim & Behçet is a later synonym of Hammatolobium lotoides Fenzl (Leguminosae: Loteae). Three species-poor genera (Hammatolobium, Tripodion, Cytisopsis) are closely related to the species-rich genus Lotus. The possibility of adopting a wider generic concept in the tribe Loteae is discussed, and it is concluded that recognizing Hammatolobium, Tripodion and Cytisopsis as three individual genera is supported by comparative morphology. The orthography of the name Hammatolobium is discussed.